Pengembangan Media Permainan Truth or Dare pada Pembelajaran Pendidikan Pancasila - Rosyada, Amrina; Hamdan, Hamdan; Krisnawati, Yuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a valid and practical Truth or Dare game for Pancasila Education learning in the fifth grade at SD Negeri 37 Lubuklinggau. The research method used R&D with the ADDIE model. The results showed that the developed product was